Adaptação transcultural e validação do Caregiver Reaction Assessment para uso no Brasil: aplicação em cuidadores informais de idosos dependentes - Mota, Fernanda Rochelly do Nascimento (2014)
This study a imed to perform the trans cultural adaptation of the Care giver Reaction Assessment (CRA ) for burden evaluation of informal caregivers of Brazilians dependent e lderly , and to verify the validity and re li a bility of the Brazilian vers ion. For this, we obtained a copy - right authorization of the authors of the ori ginal version instrument . This is a methodological and quantitative study. The five steps recommended by Beaton et al. (2007) for the transcultural adaptation were strictly carr ied : initial translat ion , synthesis of translations, backtranslation , an evaluation b y a committee of judges and pre - test, with 30 informal caregivers . The final ada pted version was sent to original authors for your approval . In the analysis of the psyc hom etric properties of the Brazilian version , we used a sample of 120 informal caregivers of dependent elderly . A group of five experts in elderly’s health area evaluated the content of the instrument and the Content Validity Index (CVI ) was calculated. The c onstruct validity was evaluated by the exploratory factor ial analysis undergoing principal components extraction with varimax rotation , and by comparison of contrasted groups with hypotheses testing , undergoing the t test for independent samples . Reliabili ty was assessed by calculating Cronbach ' s alpha coefficient . Data wer e collected through home visits , in areas of three Primary Health C are Units , in Fortaleza - CE , using, in addition to the Brazilian version of CRA , a questionnaire for characteriz ation of caregivers and elderly , Katz I ndex , Lawton and Brody Scale ( to ass ess the independence of elderly in performing Activities of Daily Living ) . Th e collected data were organized in files of Statistical Package for the Social Sciences (SPSS), version s 18.0 an d 20.0 , and su bjected to statistical analyzes , using the significance level p ≤ 0.05 for testing . This study was approved by the Federal University of Ceará Committee for Research Ethics ( Protocol N° 339.782/2013) . The rigorous process of transcultural adaptation resulted in an instrument with valid content (CVI=0.883), with factor ial structure ( five dimensions ) and behavior of items consistent with the original version , except for item 5 , originally alloca ted in physical health subscale , but in the Brazilian version , was relocated in schedule of daily activi ties subscale , where saturated with maximum factor loading . The hypotheses tested in the comparison of contrasted groups were confirmed : considering the total scale scores of the instrument , has been found that caregivers of demented elderly obtained highe r mean total scores , indicating higher burden (p = 0.001) , and caregivers who reported attending networks social support obtained lower mean total scores , denoting lower burden ( p = 0 .019) . T he instrument showed good internal consistency ( Cronbach ́s a lpha= 0.79 for the total scale ; vary ing from 0.60 to 0.84 in the five subscales ) . In conclusion, we have obtained a valid and reliable instrument, enabling the evaluation of the burden of informal caregivers of dependent elderly Brazilians. We recommended the Br azilian version of CRA in research and clinical practice as an a uxiliary instrument in evaluation of informal caregivers of dependent elderly, providing estimates of general burden, also suggest ing that the dimensions of this phenomenon dimensions that mos t affect t he lives of caregivers.